Management of Zinner’s Syndrome Associated with Contralateral Seminal Vesicle Hypoplasia: A Case Report - Mehdi Kardoust Parizi; Nasser Shakhssalim (Case Reports in Urology)
A 27-year-old man presented with chronic hematospermia, painful ejaculation, and primary infertility. Physical examination, transrectal ultrasonography, and pelvic magnetic resonance imaging (MRI) demonstrated left seminal vesicle cyst, left renal agenesia, and contralateral seminal vesicle hypoplasia. Hormone workup (LH, FSH, prolactin, and testosterone) was normal. Sperm analysis showed oligoasthenozoospermia and low ejaculate volume. We performed transurethral resection of the ejaculatory duct (TUR-ED) using methylene blue vasography guidance without surgical-related complications. Hematospermia and painful ejaculation completely improved at 2-month followup, and the patient’s wife experienced a missed abortion thereafter. This patient was considered as a rare variant of Zinner’s syndrome and was managed effectively with a less invasive treatment modality (TUR-ED).